2011
DOI: 10.1007/s10120-011-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life beyond the early postoperative period after laparoscopy-assisted distal gastrectomy: the level of patient expectation as the essence of quality of life

Abstract: Background The aim of this study was to compare the quality of life after the early postoperative period and before reaching 5 years postoperatively between patients who underwent laparoscopy-assisted distal gastrectomy (Group A) and patients who underwent open distal subtotal gastrectomy (Group B). Methods The Korean versions of the European Organization for Research and Treatment (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) and a gastric cancer-specific module, the EORTC QLQ-STO22, were used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…However, it remains unclear whether laparoscopic gastrectomy alleviates PGS. There are reports of improved postoperative QoL following laparoscopic gastrectomy[14] and also reports wherein the QoL deteriorated[15]. This difference seems to depend on the timing of the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether laparoscopic gastrectomy alleviates PGS. There are reports of improved postoperative QoL following laparoscopic gastrectomy[14] and also reports wherein the QoL deteriorated[15]. This difference seems to depend on the timing of the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, such techniques never gain much popularity, and most patients with gastric cancer at the upper part of the stomach undergo TG, in which a restricted food reservoir is inevitable. As QoL is the gap between reality and expectation,25,26 providing patients with definitive informing regarding the restrictive symptoms they need to follow after surgery for a considerable amount of time, rather than providing obscure information about symptom resolution in the indefinite future, may reduce the gap in QoL. Furthermore, QoL is the patient perception of their position in life,27 and any efforts to alter their perception would be helpful for improving QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [20] used EORTC QLQ-C30 and STO22 and reported superior HRQOL of the LAG at a mean follow-up time of 21 months. Lee et al [21] also used EORTC QLQ-C30 and STO22 and reported inferior HRQOL of the LAG at a mean follow-up time of 22 months. In all these studies, the time point for evaluation of the HRQOL had not been prespecified, and moreover the data at baseline (before surgery) were unavailable.…”
Section: Discussionmentioning
confidence: 99%